COMMUNITY PARTICIPATION IN THE MAINTENANCE OF AGRICULTURAL IRRIGATION NETWORK IN THE CIBURO NAGARI SUAYAN AREA, FIFTY KOTA REGENCY: PARTISIPASI MASYARAKAT DALAM PEMELIHARAAN JARINGAN IRIGASI PERTANIAN DI KAWASAN CIBURO NAGARI SUAYAN KABUPATEN LIMA PULUH KOTA - Muhammad Nasrullah; Lince Magriasti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The damage to the irrigation network has made farmers start to complain about watering their farms. These complaints have an effect on the interest lack of farmers to plant rice. The problem is clear, the availability of rice is decreasing in the Ciburo nagari Suayan area. Care and maintenance of irrigation networks that are lacking from the group is part of the factors in the rapid breakdown of Local irrigation networks. In the research, it is more specific how group participation in the agricultural irrigation networks maintenance in the Ciburo Nagari Suayan area and what are the impediments and enablers for group participation in maintaining agricultural irrigation networks in the Ciburo Nagari Suayan area. This study uses the theory put forward by Holil. There are three forms to see community participation, namely Participation in the form of labor, participation in the form of money, and participation in the form of property are all forms of participation. The method of research used in this research is quasi qualitative research. The research informants were selected using a technique by purposive sampling. The techniques for data collection used are observation, interviews and documentation. The research findings indicate that the form of community participation in the maintenance of agricultural irrigation networks in the Ciburo Nagari Suayan Region, Fifty Cities District is still low. This shown from the participation in the form of labor and money which is still minimal. While the inhibiting factors for group participation are the public awareness lack and socialization between officials, while the supporting factors for group participation are the will of the community and their dependence on rice yields